2010
DOI: 10.2527/jas.2008-1741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mannanase and distillers dried grain with solubles on growth performance, nutrient digestibility, and carcass characteristics of grower-finisher pigs1

Abstract: Four experiments were conducted to determine the effects of dietary supplementation of corn distillers dried grain with solubles (DDGS) diets with mannanase on performance, apparent total tract digestibility (ATTD) of energy and nutrients, blood metabolites, and carcass characteristics of grower-finisher pigs. In Exp. 1, 96 grower pigs (initial BW, 57.6 kg), 6 pigs per pen and 4 pens per treatment, were fed corn-soybean meal-based diets containing 10% DDGS and 0, 200, 400, or 600 units (U) of mannanase/kg. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
64
4
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 16 publications
8
64
4
1
Order By: Relevance
“…Rainbird et al (1984) noticed that supplementing β-mannanase resulted in a decrease in glucose and water absorption in pigs. Present findings are consistent with data reported by Yoon et al (2010) and Kim et al (2013) who observed increase in blood glucose concentrations but no effects on the total cholesterol and triacylglycerides in pigs fed diets supplemented with β-mannanase. In contrast to the report by Yoon et al (2010), Kim et al (2013) and the present results, Jo et al (2012) reported that dietary inclusion of enzyme blend containing β-mannanase to the corn-SBMbased simple diet or complex diet had no effects on blood glucose concentrations.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Rainbird et al (1984) noticed that supplementing β-mannanase resulted in a decrease in glucose and water absorption in pigs. Present findings are consistent with data reported by Yoon et al (2010) and Kim et al (2013) who observed increase in blood glucose concentrations but no effects on the total cholesterol and triacylglycerides in pigs fed diets supplemented with β-mannanase. In contrast to the report by Yoon et al (2010), Kim et al (2013) and the present results, Jo et al (2012) reported that dietary inclusion of enzyme blend containing β-mannanase to the corn-SBMbased simple diet or complex diet had no effects on blood glucose concentrations.…”
Section: Discussionsupporting
confidence: 93%
“…1 is in good agreement with data reported by Yoon et al (2010) and Kim et al (2013) who observed improvement in ADG of pigs fed diets supplemented with increasing levels of β-mannanase. The main reason that could have contributed to the influence of β-mannanase enzyme may be due to the mannan hydrolysis which can increase permeability of the cell walls and cut the long-chain polysaccharides to improve the digestibility of nutrients.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations